GRATITUDE (شكر) (Ta'limning zamonaviy transformatsiyasi, 2024)
This research thesis addresses questions such as: How should we show gratitude? Why should people be grateful? We also discuss topics such as: How does Islamic Sharia teach a person to be grateful? The thesis also takes as an example pieces from the lives of righteous people.